Development of Problem-Based Teaching Materials on Energy Sources With an ESD Approach to Improve Science Process Skills of Fifth-Grade Elementary School Students - Raudhatul Azrya; Megawati Megawati; Zulqoidi R. Habibie (FKIP - Universitas Riau, 2026)
Learning issue related to energy resources in the context of an emerging energy crisis along with energy conservation efforts, both individually and collectively, is still remain teacher-centered for Phase C elementary school students. Due to the lack of an ESD approach to sustainability related issues, these efforts resulting in limited opportunities for student to develop their SPS. This research aimed to develop a problem-based teaching materials integrated with ESD approach that is valid, practical, and effective in improving elementary students’ SPS. The research employed a R&D method, adapting ADDIE model. The effectiveness test was conducted using a one-group pre-test and post-test design with N-gain analysis on 23 fifth-grade students. The results indicated that the instructional materials fit into the categories of “highly suitable” and “suitable.” The content validation score was 82%, while the language and presentation design validation scores were 94% and 93%, respectively. The practicality assessment indicated scores of 95% from teachers and 93% from students. The mean pre-test score of 61.65 increased to 89.56 in the post-test. Furthermore, the N-gain score was 0.71, with an effectiveness rate of 71%, categorizing the developed teaching materials as quite effective.